The Influence of Outdoor Study Method in Social Studies Learning at Subang Museum on Historical Awareness and Patriotism - Nugraha, Much Luthfi Fauzan; Ruhimat, Mamat; Wiyanarti, Erlina (International Journal of Social Service and Research, 2024)
This study assesses the impact of outdoor learning methods at Subang Museum on the historical consciousness and patriotism of eighth-grade students from SMPN (State Junior High School) 1 Subang, utilizing a quasi-experimental design with an experimental and control class comprising 33 students from class 8F. Data collection involved pre-tests, post-tests, questionnaires, observation, and documentation, with statistical analyses including normality tests, homogeneity tests, mean difference tests, N-Gain score tests, and observation data tests, each briefly explained for clarity. Results demonstrate a significant increase in post-test scores for historical consciousness (50 to 75) and patriotism (49 to 74), with a significant difference observed between experimental and control groups in post-test results, despite an overall lack of statistical significance. These findings suggest that outdoor learning positively influences students' historical awareness and love for their homeland, with implications for educational practices and future research directions emphasizing the potential benefits of outdoor learning in fostering historical consciousness and patriotism.